Unexpected abnormal intraoperative neurophysiologic monitoring change by multiple spontaneous intracerebral haemorrhage during endovascular coiling. (3rd May 2020) - Lee, Sungjoon; Lee, Hyungon; Choi, Byung-Sam; Jin, Sung-Chul
Abstract: We report a patient with multiple angiographically negative intracerebral haemorrhages, which were recognized by significant changes in intraoperative neurophysiologic monitoring during the coil embolization of a left middle cerebral artery aneurysm.